Effect of AEDs on Learning and Behavior - J Gordon Millichap (Pediatric Neurology Briefs)
The literature on cognitive and behavioral impairments in children treated for epilepsy with various antiepileptic drugs (AEDs) is reviewed from the Children’s Hospital, Boston, MA.